OPTIMALISASI PERAN KOMITE SEKOLAH DALAM PERLINDUNGAN GURU DI SMP NEGERI 1 PAMARAYAN KABUPATEN SERANG BANTEN - Adang Sutarman Sutarman; Surahman Surahman (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
Less optimal role of school committee almost happened in every school, so far society perceive existence of school committee only role in terms of procurement aid of parasarana and education fund. This paper aims to explore the efforts of SMP Negeri 1 Pamarayan in optimizing the role of school committees in the protection of teachers in the implementation of education. The results of the study show that SMP Negeri 1 Pamarayan efforts always coordinate with school committees that are scheduled at least every two months, accommodate and channel the aspirations and initiatives of the community in giving birth to operational policies and educational programs, increasing responsibilities and community participation in the implementation of education, creating atmosphere and transparent, accountable, and democratic conditions. The perceived outcomes relate to teacher protection. The role of school committees in realizing teacher protection can be optimized by scheduling coordination between schools and school committees, all emerging cases can be addressed thanks to the school committee's role without causing a community reaction that harms both parties. Keywords. Optimization, School Committee, Teacher Protection